Pemanfaatan Mathverse untuk Peningkatan Pemahaman dan Motivasi Belajar Matematika Siswa SMP/MTs Di Desa Simbur Naik - Gustiningsi, Tria; Pasaribu, Feri Tiona; Perdana, Yogi; Sainuddin, Syamsir; Nusantara, Duano Sapta; Sutrimo, Sutrimo (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Mathematics is a fundamental subject for junior high school students, yet numeracy achievement in Indonesia, including in Simbur Naik Village, remains low. This community service activity aimed to improve students’ conceptual understanding and learning motivation through the implementation of the MathVerse application, which integrates Augmented Reality and Artificial Intelligence. The program involved 53 students and 6 mathematics teachers, carried out in three sessions consisting of socialization, training, and classroom implementation. The results indicated a significant improvement in cognitive achievement. The average test score increased from 49.15 to 70.67, while mastery rose from 33% to 70%. In terms of motivation, there was an increase in the indicators of effort and perceived relevance of mathematics, although interest and self-efficacy slightly declined. Student responses were highly positive, with the highest scores on the indicators of understanding and learning (82.94%) and application navigation (93.52%). Teachers also expressed consistently positive responses, with the highest rating on interest and adoption (90.63%). Documentation highlighted students’ enthusiasm in using AR and AI features, as well as teachers’ active role in facilitating the process. This activity demonstrates that MathVerse not only significantly enhances students’ conceptual understanding of mathematics but also fosters learning interest and strengthens teachers’ roles in integrating educational technology. The novelty of this program lies in the direct application of AR- and AI-based learning tools in rural schools, which are rarely reached by digital innovations. Therefore, this activity provides tangible benefits for the local education community and contributes theoretically to the effectiveness of multimedia learning and technology acceptance in mathematics education.